Lipophagy Impairment Is Associated With Disease Progression in NAFLD - Carotti, Simone; Aquilano, Katia; Zalfa, Francesca; Ruggiero, Sergio; Valentini, Francesco; Zingariello, Maria; Francesconi, Maria; Perrone, Giuseppe; Alletto, Francesca; Antonelli-Incalzi, Raffaele; Picardi, Antonio; Morini, Sergio; et al. (Frontiers in Physiology, 2020)
Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in Western countries and is associated with aging and features of metabolic syndrome. Lipotoxicity and oxidative stress are consequent to dysregulation of lipid metabolism and lipid accumulation, leading to hepatocyte injury and inflammation. Lipophagy consists in selective degradation of intracellularlipid droplets by lysosome and mounting evidence suggests that lipophagy is dysregulated in NAFLD. Here we demonstrate lipophagy impairment in experimental models of NAFLD and in a NAFLD pa-tient cohort by histomorphological and molecular analysis. High fat diet-fed C57BL/6J male mice and high-fat/high-glucose cultured Huh7 cells showed accumulation of both p62/SQSTM1 and LC3-II protein. In 59 NAFLD patients, lipid droplet-loaded lysosomes/lipolysosomes and p62/SQSTM1 clusters correlated with NAFLD activity score (NAS) and with NAS and fibrosis stage, respectively, and levels of expression of lysosomal genes, as well as autophagy-related genes, correlated with NAS and fibrosis stage. An increased amount of lipid droplets, lipolysosomes and autophagosomes was found in subjects with NAFLD compared to healthy subjects at ultrastructural level. In conclusion, here we observed that NAFLD is characterized by histological, ultrastructural and molecular features of altered autophagy that is associated with an impaired lipid degradation. Impaired autophagy is asso-ciated with features of advanced disease. Lipopolysosomes, as individuated with light microscopy, should be further assessed as markers of disease severity in NAFLD patients.